Physiotherapy management of migraine pain: facial proprioceptive neuromuscular facilitation technique versus connective tissue massage - Kurt, Aslıham; Turhan, Begümhan (Lippincott Williams and Wilkins, 2022)
Objective: Physical therapy modalities are often used by patients with migraine pain. The effectiveness of the methods in the treatment of migraine has not been clarified yet. This prospective study was planned to investigate whether facial proprioceptive neuromuscular facilitation is superior to connective tissue massage in the treatment of migraine pain. Methods: The study was conducted on 40 female patients with a neurologist-confirmed diagnosis of chronic migraine with non-aura, and who were aged between 18 and 65. They were randomly divided into 2 groups. Facial proprioceptive neuromuscular facilitation techniques were applied to the patients in the study group (Group 1), and connective tissue massage was applied to the patients in the control group (Group 2). The interventions were performed 3 times a week for approximately 20 minutes. Pain and pressure pain threshold scores were recorded on the first day of treatment before starting the session and were reassessed immediately after the end of the 18 treatment (6 weeks) sessions. Results: Pretreatment and posttreatment results were similar in both groups in terms of pain scores and pressure pain threshold values (P > 0.05). Both groups improved in pain-related outcomes (P < 0.05). Conclusions: Our results suggest that facial proprioceptive neuromuscular facilitation was no more effective than connective tissue massage for treating migraine for the sample size used in the present study. Both methods can be used in the treatment of migraine pain. © 2022 Lippincott Williams and Wilkins. All rights reserved.
Keywords: migraine disorders; migraine headache; physical therapy techniques; proprioceptive neuromuscular facilitation